Clinical diagnostic performance of droplet digital PCR for pathogen detection in patients with Escherichia coli bloodstream infection: a prospective observational study - Hiroki Kitagawa; Masato Kojima; Kayoko Tadera; Shuta Kogasaki; Keitaro Omori; Toshihito Nomura; Norifumi Shigemoto; Eiso Hiyama; Hiroki Ohge (BMC Infectious Diseases)
Abstract Background Droplet digital PCR (ddPCR) is a highly sensitive tool for detecting bacterial DNA in bacterial bloodstream infections (BSI). This study aimed to examine the sensitivity and specificity of ddPCR and the association between bacterial DNA load in whole blood and the time-to-positivity (TTP) of blood culture (BC) in patients with Escherichia coli BSI. Methods This prospective study enrolled patients with E. coli BSI confirmed via BC at the Hiroshima University Hospital from June 2023 to August 2024. The E. coli DNA load in whole blood, which was simultaneously obtained from two BC sets, was measured using ddPCR with E. coli specific primer and probe. Whole blood samples from 50 patients with BC positive for pathogens other than E. coli (n = 25) and BC negative (n = 25) were also evaluated using ddPCR. Results A total of 131 patient samples were analyzed in this study. Of the 81 patients with E. coli BSI, ddPCR detected E. coli DNA in 67 (82.7%). The results of ddPCR for E. coli had a sensitivity of 82.7% (95% CI: 73.1–89.4%), specificity 100% (95% CI: 93.0–100%). Patients with positive ddPCR results had significantly shorter TTP than those with negative results (median, 8.8 h vs. 10.7 h, p < 0.001). The positivity rate for both BC sets was significantly higher in patients with positive ddPCR results than in those with negative results (89.6% vs. 35.1%, p < 0.001). Among ddPCR-positive patients, septic shock was significantly associated with intestinal perforation, higher E. coli DNA load, higher 28-d mortality, shorter TTP, and higher positivity rate for four bottles of BC than those without septic shock. The E. coli DNA load in whole blood negatively correlated with TTP (p < 0.001, R2 = 0.38). Conclusion The E. coli DNA load in whole blood is inversely correlated with TTP. Notably, a higher E. coli DNA load is associated with septic shock.